Exploring the Nexus among the Technological Innovation, Supply Chain Integration and Environmental Management Practices in Thai Manufacturing Industry: A Sustainability View - Luedech Girdwichai; Tawee Jamjumrus; Thaniya Pongsiri; Sutas Jaepho (International Journal of Supply Chain Management, 2019)
The main focus of this paper is on the product stewardship and pollution prevention. RV suggested that the important resource for the competitive advantage is precise inter-enterprise formation through long term partnership of organization. Resource based view suggested that there are three important strategic competences sustainable development, product stewardship and pollution prevention. All the competencies have diverse environmental forces, importantly shape upon dissimilar resources, and having competitive advantages of different resources. The study has used the SEM-PLS to analyze the data collected from the manufacturing firms operating in the Thailand. the results provide the support to the view that the companies with having higher level of SCI from the whole supply chain have the benefit for the implementation of environmental management activities and also access of knowledge sharing with supply chain partners. In addition to the new technology they can implement the innovations in production and can easily met the innovative demands of customers, which eventually leads towards higher innovation performance. EMP’s and promotes the technological innovation, which can balance the cost and provide the first-mover benefit. With the deteriorating air quality, water pollution, soil pollution and other environmental issues enterprises are under pressure from government, society and supply chain members for the environmental protection. These findings suggest that precautionary and protective EMP’s can promote the technological innovation performance efficiently. Meanwhile EMP’s cost should be expanded whereas its advantages may realize in future. The short-term managers are liable to postpone investments in EMP’s. the stsuya has used the sustainable management practices to view the issue.